1996
DOI: 10.1021/bi960058j
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of Glucocorticoid Receptor and c-jun Gene Expression Is Cell Type-Specific and Exhibits Differential Hormonal Sensitivity for Down- and Up-Regulation

Abstract: We have previously proposed a novel mechanism for the coupled regulation of glucocorticoid receptor (GR) and c-jun transcription in triamcinolone acetonide (TA)-treated AtT-20 cells. This involved transcriptional interference of AP-1 (Fos/Jun)-driven gene transcription by the formation of inactive GR/Jun heterodimers. To further elucidate the molecular mechanism for GR autoregulation, the expression of GR and c-jun mRNA and protein levels were examined in both mouse L929 fibroblast cells and human CEM-C7 acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The regulation can be purely transcriptional, post-transcriptional, or both [26][27][28][29][30]. Glucocorticoid induces c-jun expression in some cells, but suppresses it in others [25,[31][32][33]. In both AtT-20 pituitary tumor cells and U-937 monocytic leukemia cells, Dex represses the transcription of c-jun [25,34].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation can be purely transcriptional, post-transcriptional, or both [26][27][28][29][30]. Glucocorticoid induces c-jun expression in some cells, but suppresses it in others [25,[31][32][33]. In both AtT-20 pituitary tumor cells and U-937 monocytic leukemia cells, Dex represses the transcription of c-jun [25,34].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore interesting that most cell types, mainly of nonlymphoid origin, appear to survive GC treatment by decreasing transcription of GR mRNA to reduce GR protein levels (9,10), and that sequences in the GR promoter seem to regulate this process (11). This down-regulation is tissue specific, because GR mRNA and protein levels were increased in the GC-sensitive human CEM-7 and mouse S49 T lymphocyte cell lines upon GC treatment (12,13), and increased GR expression was suggested to be essential for subsequent GICD in T lymphoblasts (14).…”
Section: G Lucocorticoids (Gc)mentioning
confidence: 99%
“…Only three alternative (heterogenous) non-coding exon 1s, and two of the corresponding promoter regions have been described for the hGR (Breslin & Vedeckis 1998, Breslin et al 2001. Careful examination of the gene sequence and the known hGR transcription initiation sites have shown that each previously reported initiation site has its own promoter region (Barrett et al 1996, Wei & Vedeckis 1997, Breslin & Vedeckis 1998, Breslin et al 2001, Nunez & Vedeckis 2002. Multiple independent promoter regions producing the same protein by splicing upstream of the translation initiation site, partially explain tissue-specific GR expression (Nunez & Vedeckis 2002, Pedersen & Vedeckis 2003, Pedersen et al 2004.…”
Section: Introductionmentioning
confidence: 99%